The Role of Physical Activities in Enhancing Physical Fitness Among the Community - Saefullah, Rifki; Hidayana, Rizki Apriva; Cahyandari, Rini (International Journal of Health, Medicine, and Sports, 2024)
This paper delves into the significance of engaging in sports and physical activities to improve the physical fitness of the community. The study explores the impact of physical activities on overall health and presents various strategies to promote and encourage participation in sports and exercise. The research methodology includes a comprehensive review of literature and case studies to highlight the benefits and challenges of implementing physical activities in enhancing the well-being of society. The findings emphasize the importance of early education, accessible facilities, and technological advancements in fostering a healthier and more active lifestyle. In conclusion, promoting physical activities emerges as a pivotal solution to counter the prevailing sedentary lifestyle and boost the physical fitness of the community.